Acompanhamento longitudinal do desenvolvimento físico, cognitivo, auditivo e de linguagem da criança egressa de utineonatal: contribuições da enfermagem inserida em equipe interdisciplinar - Cardoso, Sandra Maria Schefer (2017)
Prematurity, one of the leading causes of death in early childhood is an important risk factor for problems in child development. Puericulture, an area of pediatrics focused mainly on the aspects of prevention and health promotion, acts to maintain the children healthy to ensure their full development, so they reach adult life without unfavorable influences arising from intercurrences in childhood. With the technological advance observed in the medical field, more and more children considered to be extremely premature have had a chance to survive, however, it is not uncommon the presence of neurological, sensorial (hearing loss or visual) or motor sequelae, that can interfere greatly with the typical development, causing lags that will accompany the individual for life. This fact makes it necessary to follow these children through an interdisciplinary team, with the objective of detecting deviations and minimizing possible aggravations with adequate intervention. Therefore, the aim of this thesis was to accompany a group of newborn infants from a neonatal intensive care unit in a longitudinal follow-up up to three years of age, to evaluate the overall development, with emphasis on communication, considering hearing and language. The construction of the work was done by the presentation of three scientific articles directly related to the proposed theme. The first article constitutes a narrative review that addresses "Puericulture: its historical trajectory and contributions to human communication". In the second article, we analyzed the "Follow-up of the preterm in the first 36 months of life: evaluating growth and physical/motor development in ICU children who underwent newborn hearing screening". And the third study was "Auditory and language ability in neonatal ICU discharges". Throughout the narrative review, it has been possible to observe that in the last decades important and continuous changes have taken place in child care, currently focused on care models and social rights, always taking into account aspects of the organization of society. It was verified that the studied children showed, during the 36 months of follow-up, a growth and developmental lag, when compared with the normality pattern. The auditory and language skills were also lowered in the studied sample, with a significant result that points to the evidence of delay in the development of language capacity. At the end of the study, it was concluded that the importance of puericulture and the need to carry out more research on this subject were verified, mainly in order to improve the quality of comprehensive and interdisciplinary care provided to the premature child in the first three years of life.